Association of blood pressure variability and CT-based Leiden score in hypertension patients - Chen, Jianqiao; Ji, Xinqiang; Zhao, Runtao; Wang, Fan (Frontiers in Cardiovascular Medicine, 2023)
Background Blood pressure variability (BPV) obtained from ambulatory blood pressure monitoring (ABPM) has been demonstrated to accurately predict the risk of cerebrovascular events and death in hypertension patients, however, the association between BPV and the severity of coronary atherosclerotic plaque remains unclear. Methods Patients with hypertension combined with suspected coronary artery disease (CAD) were collected, who underwent both ABPM and coronary computed tomographic angiography (CCTA) from December 2017 to March 2022. Patients were divided into three groups according to the Leiden score: low-risk group (Leiden score <5), medium-risk group (Leiden score 5–20), and high-risk group (Leiden score >20). The clinical characteristics of patients were collected and analyzed. Univariate Pearson correlation and multivariate Logistics regression were used to determine the association between BPV and the severity of coronary atherosclerotic plaque. Results A total of 783 patients were included, with the average age of (62.85 ± 10.17) years and 523 males. Patients in the high-risk group had higher mean systolic blood pressure (SBP), nighttime mean SBP and SBP variability (P < 0.05). Leiden score with low risk was associated with 24 h-SBP variability (r = 0.35, P = 0.006) and 24 h-diastolic blood pressure (DBP) loading (r = −0.18, P = 0.027). Leiden score with medium and high risk was associated with nighttime mean SBP (r = 0.23, P = 0.005), 24 h-SBP variability (r = 0.32, P = 0.003), and the decrease of nighttime SBP (r = 0.24, P = 0.019). Multivariate Logistic analysis showed that smoking [odds ratio (OR) = 1.014, 95% confidential interval (CI): 1.0–1.07, P = 0.03], diabetes (OR = 1.43, 95% CI: 1.10–2.26, P = 0.01) and 24 h-SBP variability (OR = 1.35, 95% CI: 1.01–2.46, P = 0.01) were independently associated with Leiden score with medium and high risk. Conclusion Larger SBP variability in hypertensive patients indicates the higher Leiden score and consequently the more serious coronary atherosclerotic plaque. Monitoring SBP variability has certain significance for predicting the severity of coronary atherosclerotic plaque and preventing its progression.